1999
DOI: 10.1074/jbc.274.30.20895
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Expression with Light Using Caged DNA

Abstract: In this report, we describe the inactivation and sitespecific light induction of plasmid expression using a photosensitive caging compound. Plasmids coding for luciferase were caged with 1-(4,5-dimethoxy-2-nitrophenyl)diazoethane (DMNPE) and transfected into ϳ1-cm diameter sites of the skin of rats with particle bombardment. Skin sites transfected with caged plasmids did not express luciferase. However, subsequent exposure of transfected skin sites to 355-nm laser light induced luciferase expression in proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
112
0
11

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(125 citation statements)
references
References 27 publications
(24 reference statements)
2
112
0
11
Order By: Relevance
“…It is a unique report on such UCN-based delivery and photoactivation of biomolecules (nucleic acids) in solution, cells, and animal models. The DNA and siRNA photocaged with a photolabile DMNPE group was found to have a caging efficiency of 2-3%, similar to that reported previously (24). It was also demonstrated that these caged nucleic acids were efficiently loaded into the mesopores of the porous silica shell by physical adsorption, which is in agreement with recent reports elucidating the mechanism of DNA adsorption onto mesoporous silica that shows more efficient adsorption of DNA in mesoporous silica, as compared to solid silica (27).…”
Section: Discussionsupporting
confidence: 80%
“…It is a unique report on such UCN-based delivery and photoactivation of biomolecules (nucleic acids) in solution, cells, and animal models. The DNA and siRNA photocaged with a photolabile DMNPE group was found to have a caging efficiency of 2-3%, similar to that reported previously (24). It was also demonstrated that these caged nucleic acids were efficiently loaded into the mesopores of the porous silica shell by physical adsorption, which is in agreement with recent reports elucidating the mechanism of DNA adsorption onto mesoporous silica that shows more efficient adsorption of DNA in mesoporous silica, as compared to solid silica (27).…”
Section: Discussionsupporting
confidence: 80%
“…Direct, multi-site caging of mRNA 20 , 57 , 58 , 59 or DNA 21 with a reactive diazo coumarin chromophore, similar to the original caged cAMP synthesis 30 , (Bhc; Fig. 2c) efficiently inactivates the molecules.…”
Section: Caged Mrna and Dnamentioning
confidence: 99%
“…RNA is stable for at least 6 months under these conditions. Synthesis of a full-length caged pre-mRNA: branch region oligonucleotide synthesis TIMING 10 days total 24| An oligonucleotide representing the branch region of the PIP85B pre-mRNA 28 , 5¢-GGGUGCUGA*C-3¢ (A* represents 2¢-caged adenosine) is synthesized, deprotected and purified as described above for the hammerhead substrate (Steps [16][17][18][19][20][21][22][23] giving an B20% (200 nmol) yield of caged oligonucleotide as determined by UV absorption at 260 nm (a molar extinction coefficient of 124,100 M À1 for the caged RNA, including a value of 3,700 M À1 for the nitrobenzyl group, is used in this calculation) 27 .…”
Section: |mentioning
confidence: 99%
“…These experiments have involved either direct modification of pyrimidine or purine functionalities or of groups appended to them. Nonspecific caging of the phosphodiester backbone has been used to regulate gene expression in zebrafish embryos and to modulate siRNA activity in HeLa cells 20,21 . Our approach to caging the 2¢-hydroxyl functionality relies on earlier work in which the development of methods for the automated synthesis of RNA molecules necessitated strategies for protection of the reactive 2¢-hydroxyl functionality.…”
Section: Introductionmentioning
confidence: 99%